Perbandingan Kinerja Algoritma Random Forest dan Convolutional Neural Network (CNN) Untuk Klasifikasi Citra Kucing - Hilaria Iwung; Ben Rahman (Politeknik Harapan Bersama, 2026)
Cat breed classification is a significant challenge in the field of computer vision due to the high visual similarity between breeds (fine-grained classification) and pattern variations within a single breed. This study aims to compare the performance of two different machine learning approaches, namely Random Forest (RF) based on manual features and Convolutional Neural Network (CNN) based on automatic features. The research focuses on three cat breeds: Bombay, Siamese, and Persian. The research methodology uses a public dataset from Kaggle, divided in a ratio of 80:10:10. The RF pathway applies manual feature extraction through a combination of Histogram of Oriented Gradients (HOG) and Color Histogram. In contrast, the CNN pathway uses Transfer Learning techniques with the ResNet50V2 architecture. The test results show that CNN significantly outperforms RF with an accuracy of 93.33%, while RF only reaches 68.33%. The analysis shows that manual features in RF have difficulty capturing complex texture details in the Persian breed, while CNN is able to generalize well. It is concluded that the Deep Learning (CNN) approach is much more effective than traditional methods for animal breed classification.